Paul Laurence Dunbar collection ([San Francisco, Calif.] Cerebellum Corp., 2006)
The Paul Laurence Dunbar Collection is the stories of seminal American poet Paul Laurence Dunbar (1872-1906), and tells of his life and times following the Emancipation period of American History in his own words
[1] Treasured children's stories -- [2] The spirit of Frederick Douglass -- [3] Family story session.
Keywords: Paul Laurence Dunbar -- 1872-1906.